If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -2x = 3x + -2 Combine like terms: 5x + -2x = 3x 3x = 3x + -2 Reorder the terms: 3x = -2 + 3x Add '-3x' to each side of the equation. 3x + -3x = -2 + 3x + -3x Combine like terms: 3x + -3x = 0 0 = -2 + 3x + -3x Combine like terms: 3x + -3x = 0 0 = -2 + 0 0 = -2 Solving 0 = -2 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 10x-2x-60=-10x+36 | | y=3ln(2x-3)+x^2 | | 12u^2-13u+3=0 | | x-2*(-x-2)=5 | | x-2*(-x+2)=5 | | 4p+6(p+3)= | | 39.89=8g+3.97 | | (-x)-2*(3x+1)=(-x)+(-8) | | 2e=4c-16 | | 22.11=4g+3.51 | | 36.40=7g+3.71 | | 5x+-y=17 | | 62x+3=64x-1 | | -3+-6(4x+6)=-111 | | 22-10c=58+2c | | -3(5p+5)-2(1-14p)=3(5+4p) | | 7x+23y=20 | | 7+3k=31-3k | | 3x-8+5x=24 | | 3.9+8=x | | -2(5+6n)=6(8+-2n) | | -31=2+7v+4v | | 4x^2+3x-2=15 | | 21x+1+22x-2=90 | | 4x+2(x-6)=6 | | 12xy^2-55xy^2= | | 4(x+1)-2x=2x+3 | | -1+-6x+-6=-11+-7x | | 2t^2-21t+60=0 | | 7x-2y= | | 7z+7+3z-8=90 | | -3(5x-4)=-18 |